Computer coding for kids a unique step-by-step visual guide, from binary code to building games - Vorderman, Carol (London Dorling Kindersley, 2014)
Computer coding is firmly back on the agenda as a key skills for children to start learning and 'Computer coding for kids' is here to help. Avoiding computer jargon, this book guides children through creating computer programs starting with the very basics. This is a simple visual guide to get kids computer coding in no time. Computer coding is firmly back on the agenda as a key skills for children to start learning and Computer Coding for Kids is here to help. This is a unique step-by-step guide, perfect for kids interested in computer programming and how computers work. Avoiding computer jargon, this book guides children through creating computer programs starting with the very basics. Computer Coding for Kids is the only programming book that teaches both Scratch and Python programming languages, with illustrated, simple, step-by-step explanations that make the complex art of computer programming clear for the complete beginner. Starting with simple explanations of programming basics, it progresses to more advanced projects where children can build their own games. Computer Coding for Kids is ideal for kids looking to take your first steps into programming or those that are already interested and hungry to learn more
Thw World Around Us (Computer)
1 14
CHILDFENSC
Keywords: Computer programming; Programming languages (Electronic computers)